2005
DOI: 10.1074/jbc.m509647200
|View full text |Cite
|
Sign up to set email alerts
|

A Dual Function for SecA in the Assembly of Single Spanning Membrane Proteins in Escherichia coli

Abstract: The assembly of bacterial membrane proteins with large periplasmic loops is an intrinsically complex process because the SecY translocon has to coordinate the signal recognition particledependent targeting and integration of transmembrane domains with the SecA-dependent translocation of the periplasmic loop. The current model suggests that the ATP hydrolysis by SecA is required only if periplasmic loops larger than 30 amino acids have to be translocated. In agreement with this model, our data demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 58 publications
2
45
0
Order By: Relevance
“…In vivo studies showed that SRP targets IM proteins to the SecYEGDF translocon for insertion (23,60), while in vitro cross-linking of nascent IM proteins revealed contacts with Ffh, Fts, SecY, and SecA (43,52). SecA is required for the insertion of IM proteins with periplasmic loops longer than 30 amino acids (1,19,43), while single-spanning IM proteins such as PulG always require SecA, regardless of the length of their periplasmic domain (15). Consistent with this, SecA depletion almost completely abolished PrePulG* processing.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies showed that SRP targets IM proteins to the SecYEGDF translocon for insertion (23,60), while in vitro cross-linking of nascent IM proteins revealed contacts with Ffh, Fts, SecY, and SecA (43,52). SecA is required for the insertion of IM proteins with periplasmic loops longer than 30 amino acids (1,19,43), while single-spanning IM proteins such as PulG always require SecA, regardless of the length of their periplasmic domain (15). Consistent with this, SecA depletion almost completely abolished PrePulG* processing.…”
Section: Discussionmentioning
confidence: 99%
“…3 and 8). SECA (presumably SECA2) is expected to be essential to transport the long loop (;280 residues) across the membrane, based on studies in bacteria and also on the thylakoid FTSH5 (Deitermann et al, 2005;Rodrigues et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The top 750-l of the supernatant was used as an S-135 extract for cell-free protein synthesis. Preparation of Helicobacter pylori membranes was done according to the protocol designed for E. coli membranes (7). In brief, after breaking the cells using a French-pressing cell and a first centrifugation as described above, the pellet was resuspended and centrifuged for 2 h at 40,000 rpm in a Beckmann Ti50 rotor.…”
Section: Methodsmentioning
confidence: 99%